2014
DOI: 10.1111/jam.12484
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bactericidal action of acidified sodium chlorite caused by the saturation of reactants

Abstract: Aims: Factors affecting the antibacterial action of acidified sodium chlorite (ASC), a widely used disinfectant, have not been determined. This study investigated the significant factors suggesting efficient production method to maximize bactericidal action of ASC. Methods and Results: The effects of (i) preparation procedures (total three methods); (ii) initial concentrations of reactants: sodium chlorite (SC) and citric acid (CTA) (up to maximum solubility of each reactant) and (iii) final pH values (3Á0 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
3
1
0
1
Order By: Relevance
“…After 24 h there are already significant reductions on ENT counts, between lettuces washed with solutions of whey and water, and in the following days, although not significantly, they are smaller (Table 5). Nevertheless, no significant differences between all sanitizing solutions and water were found on the 7th day and sodium hypochlorite showed a reduced efficiency to control these Gram negative bacteria, which is in agreement with the reports observed in industry (Kim, Park, & Rhee, 2014).…”
Section: Resultssupporting
confidence: 91%
“…After 24 h there are already significant reductions on ENT counts, between lettuces washed with solutions of whey and water, and in the following days, although not significantly, they are smaller (Table 5). Nevertheless, no significant differences between all sanitizing solutions and water were found on the 7th day and sodium hypochlorite showed a reduced efficiency to control these Gram negative bacteria, which is in agreement with the reports observed in industry (Kim, Park, & Rhee, 2014).…”
Section: Resultssupporting
confidence: 91%
“…These results were supported by time-kill and inactivation experiments, which showed that irrespective of exposure time and concentration, the culturability of the C. jejuni isolates was completely inhibited by low concentrations of ASC. Our results are in agreement with a previous investigation where foodborne pathogens exposed to 10 ppm of ASC were not resuscitated 24 . A similar kinetic has also been observed for the inactivation of Salmonella Typhimurium following exposure to 10 ppm ASC at pH 2.5 24 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with a previous investigation where foodborne pathogens exposed to 10 ppm of ASC were not resuscitated 24 . A similar kinetic has also been observed for the inactivation of Salmonella Typhimurium following exposure to 10 ppm ASC at pH 2.5 24 .…”
Section: Discussionsupporting
confidence: 93%
“…Longer carbon lengths have been shown to reduce cytotoxicity. 8,9) Furthermore, SC penetrates bacterial cells and stops gene activity by reacting with nucleotide sulfhydryls, sulfides, and disulfides to disrupt protein synthesis, resulting in strong bactericidal effects. 10) ZC increases the production of hydrogen peroxide, which contributes to its antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%